PLANT DIVERSITY IN PARI ISLAND MARINE RESEARCH STATION OF INDONESIA SOUTH CHINA SEA: RARE PLANTS AND THEIR CONSERVATION - Sukardjo, Sukristiono; Pratiwi, Rianta (Malaysian Journal of Science, 2016)
The zones surrounding Seribu Islands Marine National Park (SMNP) are the sites of many conflicts between SMNP managers and local populations. The Pari Island represents a buffer zone of the SMNP, and their peoples have authority to utilize the island as the inalienable village lands. The flora of the island was re-enumerated in 2005 for their rare status of species present and may be considered as the entity for IBSAP (Indonesia Bio-diversity Strategy and Action Plans) 2003-2020. A 2-times check list inventory (2001 and 2005) of the island documented 174 rare plants or the biodiversity status of the small island. A checklist of 174 rare plants in the Pari Island can be used to support management purposes of SMNP. Most of the rare plants have low local density and low frequency of occurrence of spatial distributional range, and have been used to characterize rarity (A-D). A brief comment on rare plants is described and discussed in the context of the biological diversity of the island. Keywords: Botanical Exploration, Edible plants, Rare and Endangered Species, Conservation, Small Island, Indonesia.